How does innovation spirit affect R&D investment and innovation performance? The moderating role of business environment - Xingmin Yin; Luyao Qi; Jianyue Ji; Jinglin Zhou (Journal of Innovation & Knowledge (JIK), 2023)
As a vital component of entrepreneurship, innovation spirit is significant for innovation performance. Utilizing the 2015 China Micro and Small Enterprise Survey dataset, we used the Probit and Tobit micro-econometric models to study the relationship between the innovation spirit, research and development (R&D) investment, and innovation performance of micro and small enterprises (MSEs). Our research results show that the innovation spirit of MSEs has a significant promotional effect on innovation performance, and R&D investment is an important internal transmission mechanism for innovation spirit to affect innovation performance. We found that the business environment significantly moderates the impact of innovation spirit on R&D investment and innovation performance. Optimizing the business environment will suppress the impact of innovation spirit on R&D investment and enhance the promotion of innovation spirit on innovation performance. Our results have implications for policymakers about the cultivation of the innovation spirit of MSEs, the optimization of the business environment, and the improvement of the innovation ability of enterprises and the innovation vitality of the market.
Keywords: C13; D91; M21; O32; O33; O38; 650; Business environment; Innovation performance; Innovation spirit; MSEs; R&D investment